Hypersensitivity of Vagal Pulmonary Afferents Induced by Tumor Necrosis Factor Alpha in Mice - Lin, Ruei-Lung; Gu, Qihai; Lee, Lu-Yuan (Frontiers in Physiology, 2017)
Tumor necrosis factor alpha (TNFα), a pro-inflammatory cytokine, plays a significant role in the pathogenesis of allergic asthma. Inhalation of TNFα also induces airway hyperresponsiveness in healthy human subjects, and the underlying mechanism is not fully understood. A recent study reported that TNFα caused airway inflammation and a sustained elevation of pulmonary chemoreflex responses in mice, suggesting a possible involvement of heightened sensitivity of vagal pulmonary C-fibers. To investigate this possibility, the present study aimed to investigate the effect of a pretreatment with TNFα on the sensitivity of vagal pulmonary afferents in anesthetized mice. After TNFα (10 µg/kg, 0.03 ml) and vehicle (Veh; phosphate buffered saline, 0.03 ml) were administered by intra-tracheal instillation in each mouse of treated (TNF) and control (Veh) groups, respectively, the peak activity of pulmonary C-fibers in response to an intravenous bolus injection of a low dose of capsaicin (Cap; 0.5 µg/kg) was significantly elevated in TNF group (6.5 ± 1.3 impulses/s, n=12) 24-48 h later, compared to that in Veh group (2.2 ± 0.5 impulses/s, n=11; P<0.05). Interestingly, the same low dose of Cap injection also evoked a distinct burst of discharge (2.4 ± 0.7 impulses/s) in 75% of the silent rapidly adapting receptors (RARs), a subtype of RARs exhibiting no phasic activity, in TNF group, but did not stimulate any of the silent RARs in Veh group. To further determine if this sensitizing effect involves a direct action of TNFα on these sensory nerves, the change in intracellular Ca2+ concentration in response to Cap challenge was measured in isolated mouse vagal pulmonary sensory neurons. The Cap-evoked Ca2+ influx was markedly enhanced in the neurons incubated with TNFα (50 ng/ml) for ~24 h, and this sensitizing effect was attenuated in the neurons isolated from the TNF-receptor double homozygous mutant mice. In conclusion, the TNFα pretreatment enhanced the Cap sensitivity in both pulmonary C-fibers and silent RARs, and the action was mediated through TNF receptors. These sensitizing effects of TNFα may contribute, at least in part, to the pathogenesis of airway hyperresponsiveness induced by this cytokine.